The dynamic linkage between covid-19 and nutrition: a review from a probiotics perspective using machine learning and bibliometric analysis - Stefanis, Christos; Tsigalou, Christina; Bezirtzoglou, Ioanna; Mitropoulou, Gregoria; Voidarou, Chrysoula; Stavropoulou, Elisavet (Frontiers in Nutrition, 2025)
IntroductionThe pandemic crisis is now a memorable milestone in the history of science, not only for the impacts on the population’s health but also for the effort of the medical community to find immediate solutions amid the pandemic so that appropriate therapeutic means can be provided. Diet and nutrition could not fail to be studied in the context of combating the side effects of COVID-19. This study attempts to detect the relationship between dietary patterns and the disease of COVID-19 and emphasizes research on probiotics by mapping the knowledge produced during the pandemic until 2024.MethodsIn addition to bibliometrics, a machine-learning framework, ASReview, was used to structure the literature search. With this method, 2,309 articles were collected from the PubMed database, with 599 constituting inputs into bibliometric software and further analysis.ResultsFood choices, dietary patterns, vitamins and their role (vitamin D), obesity, and probiotics were keywords that attracted global research attention. Dietary supplements also constituted a field of study regarding the evolution of the disease and the impact they could have after the first pandemic wave.DiscussionProbiotics were considered an adjunct therapeutic intervention not only during the period before the development of vaccines but also alongside other therapeutic solutions. Whether used preventively or during the treatment phase, probiotics were studied to combat COVID-19 due to their potential role in immunomodulation and ability to regulate gut microbiota during respiratory infections.